Discovering Psalms : content, interpretation, reception - Creach, Jerome F. D. (Jerome Frederick Davis), 1962- (Grand Rapids, MI : Eerdmans, 2020)
This compact introduction to the interpretation of the book of Psalms encourages in-depth study of the text and genuine grappling with related theological and historical questions by providing a critical assessment of key interpreters and interpretative debates. It draws on a range of methodological approaches (author-, text-, and reader-centered) and reflects the growing scholarly attention to the reception history of biblical texts, increasingly viewed as a vital aspect of interpretation rather than an optional extra.
Introduction : the role of the Psalms in the life of the church -- Part 1. Issues in Reading the Psalms and the Psalter : -- 1. What is a psalm? -- 2. It's poetry! -- 3. Did David write the Psalms -- 4. A psalm for every occasion : types of psalms -- 5. Settings for performance of the Psalms -- Part 2. Reading the Psalms Together : -- 6. Going by the book : the Psalter as a guide to reading the psalms -- 7. The theology of the Psalms, Part 1: "The Lord reigns!" -- 8. The theology of the Psalms, part 2 : What is the human being -- Part 3. The Psalms as Prayers : -- 9. The tradition of psalmic prayer, part 1: opening fully to God -- 10. The tradition of psalmic prayer, part 2 : Psalms that pray for vengeance -- Conclusion : The Psalms and Jesus Christ
Includes bibliography (pages 190-198) and indexes.
Keywords: Bible. -- Criticism, interpretation, etc; Bible; Criticism, interpretation, etc